The impact of consulting services on small and medium enterprises: Evidence from a randomized trial in Mexico - Miriam Bruhn; Dean Karlan; Antoinette Schoar (Yale University, Economic Growth Center, 2012)
We test whether managerial human capital has a first order effect on the performance and growth of small enterprises in emerging markets. In a randomized control trial in Puebla, Mexico, we randomly assigned 150 out of 432 small and medium size enterprises to receive subsidized consulting services, while the remaining 267 enterprises served as a control group that did not receive any subsidized training. Treatment enterprises were matched with one of nine local consulting firms and met with their consultants once a week for four hours over a one year period. Results from a follow-up survey, conducted after the intervention, show that the consulting services had a large impact on the performance of the enterprises in the treatment group: monthly sales went up by about 80 percent; similarly, profits and productivity increased by 120 percent compared to the control group. We also see a significant increase in the entrepreneurial spirit index for the treatment group, a set of questions designed to illicit the SME owners' confidence in their ability to manage their business and deal with any future difficulties. However, we do not find any significant increase in the number of workers employed in the treatment group.
Keywords: D21; D24; L20; M13; O12; 330; enterprise growth; entrepreneurship; managerial capital